BIO-EFFICACY OF INSECTICIDES AGAINST SUCKING INSECT PESTS OF MOTH BEAN, VIGNA ACONITIFOLIA - G SNEHALATHA (African Journal of Environmental Economics and Management, 2025)
Investigations were carried out on bio-efficacy of insecticides against sucking pest of mothbean [Vigna aconitifolia (Jacq.) Marechal] at Pulses Research Station, Sardarkrushinagar Dantiwada Agricultural University, Sardarkrushinagar during 2017-18. The results revelead that out of Ten treatments, imidacloprid 17.8 SL @ 0.005 was found highly effective for the control of jassids and thrips at par with acetamiprid 20 SP @ 0.004% while thiomethoxam 25 WG @ 0.005 was found highly effective against white fly at par with imidacloprid 17.8 SL @ 0.005%. The control treatment of unspraying condition was found least effective for the control of jassids, white fly and thrips. The maximum yield was obtained in plots treated with thiamethoxam 25 WG @ 0.005 per cent (701 kg/ha) while minimum yield was obtained from the control treatment of unspraying condition (400 kg/ha).